Pain Management Knowledge of Registered Nurses Practicing in Acute-Care Hospitals in The Bahamas - Neely-Smith, Shane; Turner, Maggie; Curry, Zorene A.; Moxey-Adderley, Theresa E.; Wilson, Constance J.; Smith, Sandra G. (International Journal of Bahamian Studies, 2008)
Since pain is the most common complaint of the hospitalized patient, and nurses are with patients more than any other healthcare professional, it is imperative that nurses know how to adequately assess and manage patients’ pain. However, findings from studies that suggested that nurses’ lack of knowledge is among the primary reasons for inadequate pain management, which leads to major discomfort and decreased quality of life for patients. A descriptive, correlational study was conducted to describe and explore the knowledge base of registered nurses practicing in acute-care hospitals in The Bahamas in regard to pain management. The "model of nursing knowledge", developed by Jacobs-Kramer and Chinn (1988) was used as the conceptual framework for this study. The population was 247 registered nurses from three hospitals that offer acute care in The Bahamas. Data were collected via a questionnaire, which consisted of three sections: (a) six demographic items, (b) 15 multiple-choice items, and (c) 15 true or false items. Sections B and C contained items originally designed by McCaffery and Ferrell (1992), some of which were modified to reflect the pain management practices in The Bahamas. The mean pain management knowledge score was 13.5 (46.6%, se-0.20). Findings indicated that nurses lack pain management knowledge concerning physical and behavioral indicators of pain, pain assessment principles, identification of opioids/narcotics, equianalgesia and that they believe in many myths related to pain assessment and management. The results from this study reveal the need to develop strategies that will enhance pain management practices for the hospitalized patient to increase quality of life and patient satisfaction.